A construção da argumentação em redações do 9º ano do Ensino Fundamental: uma análise de provas do Saresp 2014 - Castro, Alesandra do Vale (2018)
This thesis is situated in the Reading, Writing and Teaching of Portuguese Language research line of the Program of Postgraduate Studies in Portuguese Language at the Pontifical Catholic University of São Paulo. The theme is the construction of argumentation in texts produced by the ninth grade elementary school students at the System of School Performance Assessment of the State of São Paulo (Saresp). The research question that guides this study is: How do the students of the ninth grade elementary school that participate of the Saresp organize the argumentative textual sequences and use the argumentative operators in argumentative texts? In order to answer this question, we established the general objective: to verify the argumentation in texts wrote by the ninth grade elementary school at the Saresp 2014 edition. The specific objectives are: 1) to identify, describe and analyze argumentative sequences and argumentative operators present in the analyzed texts, and 2) to discuss the relationship between sequences and argumentative operators in these texts. The mainly theoretical basis for the research is Koch (2009), Fávero and Koch (2012 [1983]), Marcuschi (2008), Cabral (2017), Travaglia (2017), and Adam (1992; 2011). The corpus is formed by thirty written productions selected among a set of one hundred texts. Here, we present the analysis of four texts as examples. The categories of analysis are textual argumentative sequences and argumentative operators. The results obtained show that, although the students write argumentative texts and use the argumentative operators, they do not aim at the effective persuasion and persuasion of the interlocutor. This perception highlights the need to develop contents and strategies of teaching writing argumentative texts that privilege the construction of the argumentation